Postpartum Depressive Symptoms and Associated Factors in Married Women: A Cross-sectional Study in Danang City, Vietnam - Van Vo, Thang; Hoa, Thi Kim Duong; Hoang, Tuyen Dinh (Frontiers in Public Health, 2017)
Introduction: Postpartum depression (PPD) amongst women is a common mental health concern. It occurrs at a time of major life change, coupled with the increased responsibilities associated with the care of a newborn infant. In Vietnam, the prevalence of depressive symptoms after giving birth has not been fully investigated. Research in the Northern provinces, in Ho Chi Minh City, and in Hue suggests postnatal depressive symptoms amongst women are common. This research aims to (1) estimate the prevalence of PPD symptoms among married women in one Vietnam city (Danang) and (2) identify the social and personal factors associated with postpartum depressive symptoms. Methods: This cross-sectional study was conducted from July 2013 to August 2014 in 10 wards of Hai Chau District, Da Nang. 600 mothers who gave birth four weeks to six months prior to being interviewed were recruited. Interviews were conducted using structured questionnaires, which included several dimensions: demographics, family living arrangements, expectations of pregnancy, expectations of infant gender, the woman’s relationship with her husband, exercise after birth, infant health and anxiety about matters other than the birth. The Edinburgh Postpartum Depression Scale (EPDS) was used to examine PPD symptoms, with a cut-off point of 12/13. Results: EPDS scores indicated the prevalence of PPD symptoms was 19.3% (95%CI: 16.16 – 22.50). Among women with PPD symptoms, 37.9% had suicidal thoughts in the previous seven days. Multivariate logistic regression indicated the following key factors were significantly associated with PPD symptoms: Not being able to rely on their husband for help, having a husband who does not spend time to discuss problems, having anxiety about matters other than the birth, not exercising after giving birth, and having an ill baby. Conclusion: These findings should be interpreted in relation to other recent research in Vietnam. A consistent pattern of prevalence estimates and associated social factors is emerging that has implications for the postpartum care of mothers.